The detection of Plasmodiophora brassicae using loop-mediated isothermal DNA amplification - Joanna Kaczmarek; Witold Irzykowski; Adam Burzyński; Małgorzata Jędryczka (Acta Agrobotanica, 2014)
Plasmodiophora brassicae, the cause of clubroot, is a very serious problem preventing from successful and profitable cultivation of oilseed rape in Poland. The pathogen was found in all main growing areas of oilseed rape; it also causes considerable problems in growing of vegetable brassicas. The aim of this work was to elaborate fast, cheap and reliable screening method to detect P. brassicae. To achieve this aim the Loop-mediated isothermal DNA amplification (LAMP) technique has been elaborated. The set of three primer pairs was designed using LAMP software. The detection was performed with the GspSSD polymerase, isolated from bacteria Geobacillus sp., with strand displacement activity. DNA extraction from clubbed roots obtained from farmers’ fields of oilseed rape infected by P. brassicae was done using a modified CTAB method. The reaction was performed for 60 min at 62oC. The visual detection was done using CFX96 Real Time PCR Detection System (BioRad) or Gerie II Amplicatior (Optigen). The detection with LAMP proved its usefulness; it was easy, fast and accurate and independent of plant age. The detection limit was 5 spores per 1 µl of the spore suspension, so LAMP was less sensitive than quantitative PCR tests reported in the literature. However, the method is cheap and simple, so it is a good alternative, when it comes to practical use and the assessment of numerous samples.